2012
DOI: 10.1080/19942060.2012.11015406
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Flow Over Circular Spillways by Using Different Turbulence Models

Abstract: Fluent software has been used to simulate flow over a circular spillway and results were compared with experimental data. As the flow over a circular spillway is turbulent and has a free surface, its characteristics are complex and often difficult to be predicted. This study assesses the performance of some turbulence models to predict the hydraulic condition of flow over circular spillways. The Volume of Fluid (VOF) method is applied to obtain the free surface in each case. Such cases include highly swirling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…The LRR (Launder-Reece-Rodi) model is one of the variants of the Reynolds Stress Models (RSM) (Greenshields, 2018). It avoids the eddy viscosity approach and determines the turbulent stresses directly by solving six transport equations attained by performing algebra on time-averaged and instantaneous Navier-Stokes equations (Hekmatzadeh, Papari, & Amiri, 2018;Rahimzadeh, Maghsoodi, Sarkardeh, & Tavakkol, 2012).…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…The LRR (Launder-Reece-Rodi) model is one of the variants of the Reynolds Stress Models (RSM) (Greenshields, 2018). It avoids the eddy viscosity approach and determines the turbulent stresses directly by solving six transport equations attained by performing algebra on time-averaged and instantaneous Navier-Stokes equations (Hekmatzadeh, Papari, & Amiri, 2018;Rahimzadeh, Maghsoodi, Sarkardeh, & Tavakkol, 2012).…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…grid was adopted, and the elbow part has an encryption treatment as depicted in Figure 2(b). According to the requirements of the wall function, the value of y+ should not be more than 1, as suggested in some studies (Keller, 1978;Rahimzadeh, Maghsoodi, Sarkardeh, & Tavakkol, 2014). Thus, the height of the first layer in the vicinity of the wall was set to 0.1 mm, and the stretching ratio was specified as 1.2.…”
Section: Geometric Structures and Fluid Parametersmentioning
confidence: 99%
“…The VOF Model is sometimes used to simulate aerator flows (Zhang, JM, Chen JG, Xu WL., 2011; Deng, J., Xu, W. L., Lei, J., and Diao, M. J., 2005; Jothiprakash, V. Y., Bhosekar, V. V., and Deolaikar, P. B., 2015; Liu, T., and Yang, J., 2014); Kökpınar, M. A., and Göğüş, M., 2002; some researchers employ the Mixture Model to study an aerator flow and found that the model is more suitable for simulating aerator flows and especially in high air-concentration regions (Rahimzadeh,H., Maghsoodi, R., Sarkardeh, H., and Tavakkol, S., 2012;Aydin, M. C. and Ozturk, M., 2009).…”
Section: Figure 1 Flow Region Over Typical Aeratormentioning
confidence: 99%